Behavioral Predictors Of Substance-Use Initiation In Adolescents With And Without ADHD - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2006)
Substance-use initiation was examined in 28 healthy adolescents and 50 with attention-deficit/hyperactivity disorder, followed longitudinally for 4 years at the National Institute of Mental Health, Bethesda, MD; National Institute on Drug Abuse, Baltimore, MD; and Neuropsychiatrie Institute, Los Angeles, CA.